1998
DOI: 10.1097/00006842-199809000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Insomniacs and Matched Normal Sleepers

Abstract: Because increased low frequency spectral power is an indicator of increased sympathetic nervous system activity, these data imply that chronic insomniacs could be at increased risk for the development of disorders, such as coronary artery disease, that are related to increased sympathetic nervous system activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
239
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(271 citation statements)
references
References 41 publications
24
239
1
7
Order By: Relevance
“…For the time domain, HRV was determined for each consecutive five-minute segment of the drive by calculating the standard deviations of time between the R-R intervals (i.e., the latency between two consecutive R waves of the ECG). This interval period is consistent with research conducted by Roche et al (1999), Bonnet et al (1998), and as described in the review of heart rate variability by van RavenswaaijArts et al (1993). The same consecutive five-minute segments were converted to the frequency domain using a fast Fourier transform (FFT) for the spectral analysis.…”
Section: Performance Measuressupporting
confidence: 91%
“…For the time domain, HRV was determined for each consecutive five-minute segment of the drive by calculating the standard deviations of time between the R-R intervals (i.e., the latency between two consecutive R waves of the ECG). This interval period is consistent with research conducted by Roche et al (1999), Bonnet et al (1998), and as described in the review of heart rate variability by van RavenswaaijArts et al (1993). The same consecutive five-minute segments were converted to the frequency domain using a fast Fourier transform (FFT) for the spectral analysis.…”
Section: Performance Measuressupporting
confidence: 91%
“…However, there is an increasing body of literature regarding the psychological and physiological differences between insomniacs and good sleepers. Several studies have demonstrated a greater prevalence of intrusive thoughts, worry, and rumination [8], poor sleep hygiene [9,10], dysregulation of the hypothalamic pituitary axis [11], elevations in sympathetic activity [12], and metabolic rate [13], increased daytime alertness [14], and elevated high-frequency electroencephalographic (EEG) activity [15][16][17] in patients with insomnia compared to good sleepers.…”
Section: Introductionmentioning
confidence: 99%
“…The sleep cycle is closely related to endocrine and metabolic functioning and to sympathovagal balance, with sleep deprivation having negative consequences for these systems. Sleep disturbances are associated with an increased concentration of cortisol and such indicators of increased sympathetic activity as elevations in pulse rate, body temperature, and epinephrine secretion (9,10). Experimentally, sleep deprivation has been shown to negatively affect glucose metabolism and to enhance variables associated with type 2 diabetes (11).…”
mentioning
confidence: 99%
“…A follow-up of a subgroup of these men was conducted in 1994 -1996 in another screening investigation called the Malmö Diet and Cancer (MDC) study (17). The mean time between initial testing and this follow-up was 15 years (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The primary aim of the original project, the methodology and general results of which have been described earlier (15,16), had been to find high-risk individuals for preventive interventions directed at cardiovascular disease, diabetes,…”
mentioning
confidence: 99%